Performance Analysis of 5G Transmission over Fading Channels with Random IG Distributed LOS Components - Dejan Jaksic; Risto Bojovic; Petar Spalevic; Dusan Stefanovic; Slavisa Trajkovic (International Journal of Antennas and Propagation)
Mathematical modelling of the behavior of the radio propagation at mmWave bands is crucial to the development of transmission and reception algorithms of new 5G systems. In this study we will model 5G propagation in nondeterministic line-of-sight (LOS) conditions, when the random nature of LOS component ratio will be observed as Inverse Gamma (IG) distributed process. Closed-form expressions will be presented for the probability density function (PDF) and cumulative distribution function (CDF) of such random process. Further, closed-form expressions will be provided for important performance measures such as level crossing rate (LCR) and average fade duration (AFD). Capitalizing on proposed expressions, LCR and AFD will be discussed in the function of transmission parameters.